The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1177/15330338211019504
|View full text |Cite
|
Sign up to set email alerts
|

RNA Binding Protein-Based Model for Prognostic Prediction of Colorectal Cancer

Abstract: Background: Colorectal cancer (CRC) is a kind of gastrointestinal tumor with serious high morbidity and mortality. Several reports have implicated the disorder of RNA-binding proteins (RBPs) in plenty of tumors, associating it to tumorigenesis and disease progression. The study is intended to construct novel prognostic biomarkers associated with CRC patients. Methods: Data of gene expression was acquired from the TCGA database, prognosis-related genes were selected. Besides, we analyzed GO and KEGG pathways. U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…PLEKHA8P1 expression has been associated with the development and progression of many malignancies in humans, such as CRC and renal cancer [ 33 ]; moreover, research has shown that its dysregulated expression affects 5-Fluorouracil-induced chemoresistance in the human hepatocellular carcinoma cell line FT3-7 [ 34 ]. Prior studies found ZC3H12A has links with immune homeostasis and post-transcriptional regulation which can stimulate tumor progression in lung and colon cancer [ 35 37 ]. LPO can collaborate with activated Wnt signaling to induce intestinal neoplasia [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…PLEKHA8P1 expression has been associated with the development and progression of many malignancies in humans, such as CRC and renal cancer [ 33 ]; moreover, research has shown that its dysregulated expression affects 5-Fluorouracil-induced chemoresistance in the human hepatocellular carcinoma cell line FT3-7 [ 34 ]. Prior studies found ZC3H12A has links with immune homeostasis and post-transcriptional regulation which can stimulate tumor progression in lung and colon cancer [ 35 37 ]. LPO can collaborate with activated Wnt signaling to induce intestinal neoplasia [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Kaplan–Meier survival plots, receiver operating characteristic (ROC), C-index and DCA curves, visualized by R package“survival”, “timeROC”,“ggDCA” and “survminer”, were used to evaluate prognostic value of risk model in colon cancer. The constructed model in this study was also compared with known models in predicting the prognosis of colon patients ( Huang et al, 2018 ; Li et al, 2021 ; Liang et al, 2021 ). Univariate and multifactor analyses were performed to determine the independent prognostic value of the risk model.…”
Section: Materials Methodsmentioning
confidence: 99%
“…Apart from this study, colorectal cancer is the most studied malignancy in relation to the CELF4 expression level and mutations. In this context, CELF4 has been identified as one of the reproducible prognostic RBPs in multiple investigations; however, the results are controversial [100][101][102][103]. CELF4 downregulation in colorectal cancer samples is detected through analysis of the Cancer Genome Atlas database (TCGA).…”
Section: Other Celf Membersmentioning
confidence: 99%
“…This gene, along with other RBP genes, has created a survival-related network with remarkable prognostic value [100][101][102]. On the other hand, the predictive study of the characteristics of RBPs in colorectal cancer highlights the significant role of CELF4 as an overexpressed transcript in highly metastatic SW620 cell lines [103].…”
Section: Other Celf Membersmentioning
confidence: 99%